Olive oil consumption is associated with a lower risk of cardiovascular disease and stroke. Issue 1 (January 2022) - Donat-Vargas, Carolina; Sandoval-Insausti, Helena; Peñalvo, José L.; Moreno Iribas, Maria Concepción; Amiano, Pilar; Bes-Rastrollo, Maira; Molina-Montes, Esther; Moreno-Franco, Belén; Agudo, Antonio; Mayo, Cristina Lasheras; Laclaustra, Martín; De La Fuente Arrillaga, Carmen; et al.
Summary: Background & aims: The specific association of olive oil consumption with coronary heart disease (CHD) or stroke has not been totally established. Objective: to examine whether olive oil consumption is associated with subclinical atherosclerosis, the risk of total cardiovascular disease (CVD), CHD, and stroke. Methods: Three cohorts were included: AWHS (2318 men), SUN Project (18, 266 men and women), and EPIC-Spain (39, 393 men and women). Olive oil consumption was measured at baseline using validated questionnaires. Results: In the AWHS, 747 participants had a positive coronary artery calcium score (CACS>0), and the OR (95% CI) was 0.89 (0.72, 1.10) in those with virgin olive oil consumption ≥30 g/day ( v. <10 g/day). In the SUN Project (follow-up 10.8 years) 261 total CVD cases occurred, and the HR was 0.57 (0.34, 0.96) for consumptions ≥30 g/day ( v. <10 g/day). In the EPIC-Spain (follow-up 22.8 years) 1300 CHD cases and 938 stroke cases occurred; the HRs for stroke according, 0 to <10 (ref), 10 to <20, 20 to <30, and ≥30 g/day of olive oil consumption, were 0.84 (0.70, 1.02), 0.80 (0.66, 0.96), 0.89 (0.74, 1.07). A weaker association was observed for CHD. The association was stronger among those consuming virgin olive oil, instead of common (refined). Conclusions: Olive oil is associated with lower risk of CVD and stroke. The maximum benefit could be obtained with a consumption between 20 and 30 g/day. The association could be stronger for virgin olive oil and might operate from the early stages of the disease.